LEAVE MANAGEMENT SYSTEM USING WEB SERVICE WORKER AND CHUNKING OF IMAGE SUBMISSION - C. Mama, Jasmin Jeanette; Garillo, Christian L. (International Journal of Multidisciplinary Research and Studies, 2022)
Filing a leave of absence is typical for any employee. Employees may be required to submit applications which must be fully accomplished before approval. The aim of this project is like a document tracking system for leave applications through a web application. A responsive web application for leave management system where the applicant will know the status of his/her request. The administration will then be notified if there are requests submitted to them. What makes this project efficient is the incorporation of the service worker, a cutting-edge technology, in web development. A service worker is a type of web worker. It is essentially a JavaScript file that runs separately from the main browser thread, intercepting network requests, caching or retrieving resources from the cache, and delivering push messages. [1] Since service workers run separately from the main thread, workers are independent of the application they are associated with. Some parts of the project are usable offline using the HTTP request. Since leave applications may have image attachments, this system will make it possible to submit images in chunks. Chunking of images is important because there are instances where uploading may fail due to large files or a slow internet connection. The use of web service workers provides the accessibility of the application even offline. While chunking of images makes it possible to submit images even on slow connectivity. The implementation of online leave management is geared toward making leave applications simple and convenient and is readily accessible for both the management and the employee.